Electromagnetic Field Matter Interactions in Thermoelasic Solids and Viscous Fluids - Hutter, Kolumban; Ven, Alfons A.F; Ursescu, Ana (Lecture Notes in Physics,, 2006)
This book in two parts delivers a thorough derivation of nonrelativistic interaction models of electromagnetic field theories with thermoelastic solids and viscous fluids, the intention being to derive unique representations for the observable field quantities. Part I, a revised and updated version of LNP 88 "Field Matter Interactions in Thermoelastic Solids," investigates the foundations and the equivalence of various formulations of the interaction of the electromagnetic field with thermoelastic solids in the classical continuum physics limit, while Part II extensively surveys two major fields of applications, namely, magnetoelastic instabilities and vibrations, and electrorheological fluids. This volume is intended for and will be useful to students and researchers working on all aspects of electromagneto-mechanical interactions in the materials sciences of complex solids and fluids.